Association between Hypocalcemia and Outcome in COVID-19 Patients: A Retrospective Study - Patidar, Bhagwan Singh; Mukhopadhyay, Tapasyapreeti; Subramanian, Arulselvi; Aggarwal, Richa; Soni, Kapil Dev; Nischal, Neeraj; Sahoo, Debasis; Surbhi, Surbhi; Wig, Naveet; Pandey, Ravindra Mohan; Malhotra, Rajesh; Trikha, Anjan (Journal of Laboratory Physicians, 2022)
Background Calcium has been shown to play a vital role in the pathophysiology of severe acute respiratory syndrome-coronavirus-2 and middle east respiratory syndrome coronavirus diseases, but less is known about hypocalcemia in coronavirus disease 2019 (COVID-19) patients and its association with the disease severity and the final outcome. Therefore, this study was conducted with an aim to assess clinical features in COVID-19 patients having hypocalcemia and to observe its impact on COVID-19 disease severity and the final outcome.Methods In this retrospective study, consecutive COVID-19 patients of all age groups were enrolled. Demographical, clinical, and laboratory details were collected and analyzed. On the basis of albumin-corrected calcium levels, patients were classified into normocalcemic (n = 51) and hypocalcemic (n = 110) groups. Death was the primary outcome.Results The mean age of patients in the hypocalcemic group was significantly lower (p < 0.05). A significantly higher number of hypocalcemic patients had severe COVID-19 infection (92.73%; p < 0.01), had comorbidities (82.73%, p < 0.05), and required ventilator support (39.09%; p < 0.01) compared with normocalcemic patients. The mortality rate was significantly higher in the hypocalcemic patients (33.63%; p < 0.05). Hemoglobin (p < 0.01), hematocrit (p < 0.01), and red cell count (p < 0.01) were significantly lower with higher levels of absolute neutrophil count (ANC; p < 0.05) and neutrophil-to-lymphocyte ratio (NLR; p < 0.01) in the hypocalcemic patients.Albumin-corrected calcium levels had a significant positive correlation with hemoglobin levels, hematocrit, red cell count, total protein, albumin, and albumin-to-globulin ratio and a significant negative correlation with ANC and NLR.Conclusion The disease severity, ventilator requirement, and mortality were considerably higher in hypocalcemic COVID-19 patients.
Keywords: calcium; coronavirus; mortality; neutrophil-to-lymphocyte ratio; pandemic